Description of Family Behavior in preventing Osteoarthritis in Sianipar Sihailhail Village, Balige District - Sitorus, Jenti; Nainggolan, Elfrida (Sean Institute, 2023)
Osteoarthritis is a clinical syndrome characterized by damage or disruption of the articular cartilage, subchondral bone, joint surfaces, synovium and para-articular tissue, with characteristics of progressive thinning of the cartilage, accompanied by the formation of new bone at the joint edges (osteophytes) and subchondral trabeculae. . Osteoarthritis is a problem that is often encountered in society nowadays. This can be caused by changes in lifestyle and an increase in the life expectancy of the Indonesian population. Along with developments over time, people's lifestyles have also changed. Lifestyle changes that require everything to be done quickly, both in terms of transportation and diet, are also one of the trigger factors for the emergence of Osteoarthritis. The research in this study uses a descriptive research method which aims to determine the description of family behavior in preventing osteoarthritis in Sianipar Sihailhail village, Balige district.The sampling technique used was incidental sampling, so the number of samples that met the criteria was 32 people. The majority of families' knowledge in preventing Osteoarthritis was good, 20 people (62.5%), the majority of families' attitudes in preventing Osteoarthritis were poor, 18 people (56.25%) and Family Action in preventing Osteoarthritis is sufficient for the majority of 20 people (62.5%). Researchers hope that more families will seek information about how to prevent Osteoathritis..